Correlation between Endoscopic and Histopathological Findings in Gastric Lesions - Poudel, A; Regmi, S; Poudel, S; Joshi, P (Journal of Universal College of Medical Sciences, 2013)
INTRODUCTION: Stomach is an important site for wide variety of lesions which include congenital, inflammatory and neoplastic conditions. Helicobacter pylori(H. pylori) has been implicated in varied range of gastric lesions including Gastritis, Peptic Ulcer (PU), Gastric Adenocarcinoma and Gastric Lymphoma. MATERIAL AND METHODS: A total of 43 gastric biopsies were studied retrospectively over a period of 5 months from March to July 2013 at Department of Pathology, Universal College of Medical Sciences Teaching Hospital, Bhairahawa. RESULTS: Out of these 43 cases, 29 (67.4%) were male and 14 (32.6%) were female with a male to female ratio of 2.07:1. According to the endoscopic findings, out of 43 cases, 25 (58.1%) cases had Gastritis, 5 (11.63%) had Peptic Ulcer, 4 (9.30%) had gastric Carcinoma, 4 (9.30%) had Chronic Gastritis (CG) with Atrophy, 3 (6.97%) had Erosive Gastritis and 2 (4.7%) had normal mucosa. The correlation of endoscopic and histopathological diagnosis of these gastric lesions was 34.88%. CONCLUSION: It was observed that endoscopic diagnoses of gastric lesions poorly correlated with those of histopathological diagnoses. H. pylori has a high prevalence in our region and is mostly associated with Intestinal Metaplasia (IM), CG and Atrophic Gastritis (AG). DOI: http://dx.doi.org/10.3126/jucms.v1i3.8763 Journal of Universal College of Medical Sciences Vol.1(3) 2013: 37-41